How Political Orientation and Vulnerability Shape Representations of the Economic Crisis in Greece and Italy. Issue 1 (5th April 2017) - Mari, Silvia; Volpato, Chiara; Papastamou, Stamos; Chryssochoou, Xenia; Prodromitis, Gerasimos; Pavlopoulos, Vassilis
In the current research, we investigated the lay representations of the recent economic downturn, that had severe consequences on the lives of the involved people. We compared data of respondents from two countries that were affected to a different degree by the crisis: Greece ( N = 529) and Italy ( N = 327). We examined laypeople's representations of the perceived causes of the crunch (e.g., overconsumption, obscure power conspiracy), the strategies that are believed to be useful to overcome it (e.g., conforming to EU request, EU exit), and the political participatory activities (e.g., legal and illegal activism) that people intend to adopt. These variables were analyzed in light of two main predictors: political orientation and subjective economic vulnerability. The main hypothesis was that self-positioning on the left/right axis may be a strong driver of lay representations and political participation. However, we expected that in conjunction with the linear effect of this variable, its quadratic effect should be considered as well. The latter specifies that in some circumstances the opinions of people self-positioned at the poles of the political spectrum may be closer to each other than to the opinions of the people that position themselves in the center which sometimes do not behave as moderate but appear more conformist. Additionally, we hypothesized that vulnerability may be a motive to seek for explanations of the crisis, to find strategies and to engage in activities to overcome it. Findings were generally in line with predictions and were discussed in the light of recent research and the context of analysis.